Author Correction: Dipeptidyl peptidase-4 inhibitors and cancer risk in patients with type 2 diabetes: a meta-analysis of randomized clinical trials. Issue 1 (December 2017) - Zhao, Ming; Chen, Jiayi; Yuan, Yanyan; Zou, Zuquan; Lai, Xiaolong; Rahmani, Daud; Wang, Fuyan; Xi, Yang; Huang, Qin; Bu, Shizhong
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.